Exit Polls, Turnout, and Bandwagon Voting: Evidence from a Natural Experiment - Rebecca B. Morton; Daniel Müller; Lionel Page; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2013)
We exploit a voting reform in France to estimate the causal effect of exit poll information on turnout and bandwagon voting. Before the change in legislation, individuals in some French overseas territories voted after the election result had already been made public via exit poll information from mainland France. We estimate that knowing the exit poll informa- tion decreases voter turnout by about 12 percentage points. Our study is the first clean empirical design outside of the laboratory to demonstrate the effect of such knowledge on voter turnout. Furthermore, we find that exit poll information significantly increases bandwagon voting; that is, voters who choose to turn out are more likely to vote for the expected winner.
Keywords: 330